An investigation of factors reducing seat belt use amongst Spanish drivers and passengers on urban roads - Cunill, M; Gras, M.E; Planes, M; Oliveras, C; Sullman, M.J.M (Accident analysis and prevention, 2004)
Seat belt use on Spain’s highways is more than 80%, while on the urban roads this figure is around 50%. As there was little information available to explain the difference in seat belt use rates, the main aim of this study was to investigate why there is a lower rate of seat belt use on urban roads. A number of perceptions, beliefs and expectancies about seat belt use were examined to identify variables that discriminated between seat belt users and non-users on urban roads. The subjects were 398 undergraduate students (aged 17–47) studying at the University of Girona, Spain. On the urban roads reported discomfort from using the seat belt was higher, while perceptions of risk (for non-users), safety perceptions (for those using a seat belt), beliefs about the seriousness of a crash or the effectiveness of the seat belt were all lower than on the highway. Perceptions of safety, discomfort, and social influence predicted seat belt use on urban roads. Concern about being fined for not using a seat belt did not predict seat belt use. The results of this research suggest that in order to increase seat belt use on urban roads, the issue of discomfort must be addressed. In addition, prevention campaigns should include information about the effectiveness of the seat belt in preventing/reducing injuries or deaths on urban roads. The results also highlight the importance of social influence for determining seat belt use/non-use and the potential role social influence could play in increasing seat belt usage.